RELIABILITY-CENTERED MAINTENANCE (RCM) EVALUATION METHOD IN THE INDUSTRY APPLICATION, CASE STUDY: FERTILIZER COMPANY, INDONESIA - Khasanah, Rahayu; Dawal, Siti Zawiah Md.; -, Jamasri (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2015)
Nowadays, Reliability-centered Maintenance (RCM) has become the solution to determine the type of maintenance tasks and inspections needs to be performed to the assets in achieving effective and efficient maintenance. However, implementing RCM is not enough to achieve optimization of maintenance planning. The evaluation, as one of the important point should be done to prove the benefits of RCM and to continuously improve the maintenance planning. In this study, the effects of RCM implementation in the industry application were evaluated, as a step for continuous improvement in RCM application. The case study is an Ammonia plant in a fertilizer company in Indonesia. This research evaluates the RCM effects by investigating and analyzing Downtime Loss and Mean Time between Failures (MTBF). The problems in RCM implementation in the case study also investigate as a basic for giving the recommendation to the company as a way to improve the RCM implementation. In general, the findings from the investigation of case study affirm that RCM implementation do improve the plant performance which are showed by decreasing of Downtime Loss and Mean Time between Failures. The significant problems that become pitfalls in RCM implementation process are about the worker’s culture and understanding on the RCM process. Overall, the study shows that RCM implementation brings many benefits to the company by decreasing the Downtime Loss and Mean Time between Failures which can be resulted as the higher profit for the company.